Differences in the Seroprevalence of SARS-CoV-2 in Children from Confirmed Covid-19 Healthworkers with or without Symptoms in RSUP Dr.Mohammad Hoesin Palembang - Silitonga, Enggrajati; Iriani, Yulia; Kamila, Ariesti; Damayanti, Moretta (Journal of Social Research, 2025)
The surge of COVID-19 cases in June 2021 underscored the role of healthcare workers (HCWs) as potential sources of household transmission, including to their children. This study aimed to analyze the differences in SARS-CoV-2 seroprevalence among children of HCWs at RSUP Dr Mohammad Hoesin Hospital, Palembang, based on parental symptom status, and to identify influencing factors. A cross-sectional study was conducted involving 61 children of HCWs confirmed with COVID-19. SARS-CoV-2 IgG levels were measured using the Chemiluminescence Microparticle Immunoassay (CMIA). Statistical analyses included Chi-square/Fisher’s exact tests and logistic regression. Results showed that 86.8% of subjects had reactive IgG, with 54.1% being children of symptomatic HCWs. The mean age was 6.9 (±3.18) years, with a male-to-female ratio of 1.3:1. While seroprevalence did not differ significantly between groups (p=0.079), IgG levels were significantly higher in children of symptomatic HCWs (median 3112 AU/ml vs. 758.9 AU/ml, p=0.02). Symptomatic children also had higher median IgG levels (3270 AU/ml vs. 1324 AU/ml). A strong negative correlation was found between parental CT-value and child’s IgG level (r = -0.64, p=0.001). Multivariate analysis identified CT-value as the sole significant risk factor for seroprevalence (p=0.003, AUC=100%). In conclusion, although seroprevalence did not differ, IgG levels were significantly higher in children of symptomatic HCWs, with parental viral load (CT-value) being the key determinant of seropositivity.